Pearl Harbor - Swanson, Jennifer; McMorris, Kelley; Larson, Kirby (New York, NY : Scholastic Inc., 2018)
"Pearl Harbor features real stories of that fateful Sunday morning in 1941 when Japanese planes executed a surprise attack on the American base at Pearl Harbor in Hawaii. American Girl Nanea Mitchell shares her own experiences adjusting to the drastic changes to everyday life in Hawaii following the attack"--Amazon.
Island paradise -- The melting pot -- Celebrations and negotiations -- A daring plan -- Surprise attack! -- An Island on fire -- Under military control -- Americans of Japanese ancestry -- Kokua.
"Nanea"--Cover.
Includes bibliographical references.
Age 7-10.
Grade 4 to 6.
Keywords: 1939-1945; Pearl Harbor (Hawaii), Attack on, 1941 -- Juvenile literature; World War, 1939-1945 -- Causes -- Juvenile literature; Pearl Harbor (Hawaii), Attack on, 1941.; World War, 1939-1945 -- Causes; Pearl Harbor (Oahu, Hawaii), Attack on, 1941.; Diplomatic relations; War -- Causes; Japan -- Foreign relations -- United States -- Juvenile literature; United States -- Foreign relations -- Japan -- Juvenile literature; United States -- Foreign relations -- Japan; Japan -- Foreign relations -- United States; Hawaii; Japan; United States; Juvenile works; Literature